2015
DOI: 10.1108/jeim-12-2013-0092
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of cognition and emotion in IS usage

Abstract: Access to this document was granted through an Emerald subscription provided by emeraldsrm:198285 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Of the four sub-attributes, compatibility, ease of use, relative superiority, and quality of service, only ease of use does not have significant positive effects. Several studies have compared ease of use during pre-and post-adoption of information systems and found that ease of use results tend to be inconsistent with regard to attitudes on pre-adoption and becomes insignificant in post-adoption installations (Yang & Bahli, 2015). involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Of the four sub-attributes, compatibility, ease of use, relative superiority, and quality of service, only ease of use does not have significant positive effects. Several studies have compared ease of use during pre-and post-adoption of information systems and found that ease of use results tend to be inconsistent with regard to attitudes on pre-adoption and becomes insignificant in post-adoption installations (Yang & Bahli, 2015). involvement.…”
Section: Discussionmentioning
confidence: 99%
“…The cognitive RSQ means the extent to which retailers' effective and efficient return service is perceived by customers when customers develop an ultimate feeling in the return process (Parasuraman et al, 2005). While what a customer "knows" and whether the received services exceed his/her expectations show the cognitive component of attitude, what he/she "feels" is the affective component of attitude (Yang and Bahli, 2015). From the consideration of cognitive paths, customer loyalty is determined by the retailer's functional return service value perceived by customers and the relational benefits from retailer's return service perceived by customers (Wong et al, 2019).…”
Section: Impacts Of Return Channel Typementioning
confidence: 99%